2015
DOI: 10.3748/wjg.v21.i24.7478
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver markers are associated with higher risk of type 2 diabetes

Abstract: Higher levels of GGT and ALT and lower AST/ALT within the physiological range are independent, additive risk factors of T2DM and IFG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 38 publications
8
47
1
Order By: Relevance
“…The present prospective study is consistent with and extends the findings of previous cross-sectional studies 15,16 . Adjustment for additional variables, such as fasting insulin and fasting blood glucose, was also carried out.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present prospective study is consistent with and extends the findings of previous cross-sectional studies 15,16 . Adjustment for additional variables, such as fasting insulin and fasting blood glucose, was also carried out.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, it would be clinically relevant to examine the simultaneous elevation of ALT and GGT levels, and its relationship with the development of type 2 diabetes mellitus incidence. Although previous cross‐sectional studies have shown that the combination of higher GGT and ALT had a positive association with type 2 diabetes mellitus, prospective studies on that issue are limited. As a statistically significant association does not necessarily indicate usefulness for prediction, we also evaluated the incremental predictive value of the liver enzymes.…”
Section: Introductionmentioning
confidence: 98%
“…In this context, it is important to mention that elevated levels of serum GGT, as here induced by PCB126 exposure, have been also considered an early biomarker for development of DM2373839. Furthermore, PCB126 exposure up-regulated the expression of GLUT-4 in the retroperitoneal adipose tissue, which was accompanied by marked reduction of insulin sensibility and elevated levels of serum insulin.…”
Section: Discussionmentioning
confidence: 87%
“…2C), suggesting that lipid accumulation was specific to the liver. Moreover, alanine transaminase (ALT) and aspartate transaminase (AST) activity, which are two of the most reliable markers of hepatocellular injury20, were 45.6% and 23.4% higher, respectively, in the serum of Pld1 −/− mice than in Pld1 +/+ mice, indicating that liver dysfunction occurred in the Pld1 −/− mice (Table 1). These data indicate that PLD1 deficiency specifically induces lipid accumulation in the liver.…”
Section: Resultsmentioning
confidence: 99%